Rapid Identification of the Candida Species From Direct Blood Cultures by CHROMAgar™ Candida - Birinci, A.; Akkurt, L.; Acuner, I.Ç.; Unlu, M.; Durupínar, B. (Cambridge Medical Publications, 2004)
We evaluated the ability of CHROMagar™ Candida to identify Candida species isolated directly from blood cultures. A total of 50 clinical isolates of Candida were incubated at 35°C, and once growth was established, an aliquot of each was plated onto CHROMagar™ Candida medium. A control specimen was plated directly from Sabouraud's dextrose agar. Following incubation at 30°C, all yeast isolates were identified by colony morphology and colour. We were able to identify all isolates of C. albicans (n = 20), C. tropicalis (n = 14), C. glabrata (n = 6), and C. krusei (n = 5), which were isolated from blood or from control cultures. This study demonstrated that CHROMagar™ Candida reliably isolated and identified yeast taken directly from blood cultures. We conclude that this rapid and easy method of identifying Candida species will enable clinicians to quickly choose the appropriate antifungal agent. This should decrease patient morbidity and mortality.
Keywords: Blood Culture; Candida; CHROMagar™ Candida; Identification